Pengaruh Net Profit Margin, Return on Asset, Return on Equity, Dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Andika Fahruzzi; Dedi Hariyanto; Heni Safitri (Universitas Muhammadiyah Pontianak, 2018)
This study aims to determine how much the effect of the company's financial performance focused on Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS) to Stock Price on Manufacturing Company of Consumer goods Industry Sector Listed in BEI as of 31 December 2016. The sampling technique used in this research is saturated sampling method and the sample used is 37 companies. The analysis technique used is Multiple Linear Regression, Correlation Coefficient, and Coefficient of Determination. Hypothesis Examination used F- test simultaneously and Hypothesis Examination used t-test partially. The Result of simultaneous test (F-test) indicate that independent variable that is NPM, ROA, ROE and EPS together have no significant effect on attached variable Stock Price on Manufacturing Company of Consumer goods Industry Sector Listed in BEI as of 31 December 2016. The partial test (t test) of NPM ROA ROE variable has no significant effect on the Stock Price on Manufacturing Company of Consumer goods Industry Sector Listed in BEI as of 31 December 2016. And the EPS variable has a significant effect on the Stock Price on Manufacturing Company of Consumer goods Industry Sector Listed in BEI as of 31 December 2016.